High DC gain self‐cascode structure of OTA design with bandwidth enhancement. Issue 9 (4th April 2016) - Xu, Daiguo; Liu, Lu; Xu, Shiliu
Abstract : A high DC gain self‐cascode structure of operational transconductance amplifier (OTA) design with bandwidth enhancement is proposed. Based on the concept of self‐cascode structure, which provides high output resistance and transconductance, the proposed OTA presents a compensation methodology to obtain better unity‐gain bandwidth. The proposed OTA is compared with previous structures, with the same size of input/output transistors and compensation capacitance as well as load capacitance, and simulation results show a DC gain enhancement of >20% and 2.4 times unity‐gain bandwidth at the same time, and the performances of the proposed OTA bring a better figure of merit (FOM).